The mysterious benedict society ebook - Stewart, Trenton Lee (The Mysterious Benedict Society, 2008)
For fans of Lemony Snicket and Escape from Mr. Lemoncello's Library , this first book in the bestselling, award-winning Mysterious Benedict Society series is not to be missed! "Are you a gifted child looking for special opportunities?" Dozens of children respond to this peculiar newspaper ad and are then put through a series of mind-bending tests, which readers take along with them. Only four children—two boys and two girls—succeed. Their challenge: to go on a secret mission that only the most intelligent and inventive children could complete. To accomplish it, they will have to go undercover at the Learning Institute for the Very Enlightened, where the only rule is that there are no rules. But what they'll find in the hidden underground tunnels of the school is more than your average school supplies. So, if you're gifted, creative, or happen to know Morse Code, they could probably use your help.